Time spent on smartphones are associated with exposure to online tobacco advertisements among youths - Heewon Kang (Tobacco Induced Diseases, 2019)
Objective Smartphones are considered a double-edged sword in the tobacco control field. Ideally, the device can be used for efficiently delivering prevention and cessation programs. However, there are also concerns adolescents may be receiving pro-smoking messages via smartphones. This study aimed to examine the association between time spent on smartphones and exposure to online tobacco advertisements among youths.